Integration of physical and genetic maps of common bean through BAC-derived microsatellite markers - Córdoba, J.M.; Chavarro, C; Schlueter, JA; Jackson, S.A.; Blair, Matthew W. (Springer, 2010)
Background: Common bean (Phaseolus vulgaris L.) is the most important legume for direct human consumption and the goal of this study was to integrate a recently constructed physical map for the species with a microsatellite based genetic map using a BAC library from the genotype G19833 and the recombinant inbred line population DOR364 × G19833.